Penerapan Model Pembelajaran Kooperatif Tipe Teams Games Tournament Berbantuan Media Teka-Teki Silang Dalam Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi - Nadiyanti, Rani; Gumilar, Gugum; Kurniawan, Kurniawan (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This study was motivated by the low student learning outcomes in economic subjects. The aim is to determine the improvement of student learning outcomes in economic subjects through the application of the Teams Games Tournament type cooperative learning model assisted by Crossword media. The method used is quasi-experiment and nonequivalent control group design, and data collection techniques through tests in the form of multiple choice questions. The study population was all XI social studies students at SMAN 7 Tasikmalaya in the 2022/2023 school year which amounted to 199 students. The samples used were XI IPS 1 class as an experimental class totaling 33 students and XI IPS 5 class as a control class totaling 35 students, which were selected using nonprobability sampling technique purposive sampling type. The results of this study indicate that: 1) there are differences in student learning outcomes in the experimental class with an average pretest score of 41.67 increasing to 88.25 on the posttest. 2) there are differences in student learning outcomes in the control class with an average pretest score of 40.54 increasing to 78.26 in the posttest. 3) there is a difference in the improvement of student learning outcomes between the experimental class and the control class with a Sig. (2-Tailed) of 0.000 <0.05. Thus, the application of the TGT type cooperative learning model assisted by Crossword media has a high level of effectiveness in improving student learning outcomes in economic subjects.